Carbon-based dot-capped gold nanoparticles hybridized with manganese dioxide for enhanced photodynamic cancer therapy. (7th December 2022) - Hu, Rongjing; Guo, Tianmin; Zeng, Chenyi; Chen, Mingming; Zhu, Xiajun; Chen, Lichan; Dong, Yongqiang; Fu, FengFu
Abstract : Composite material nanohybrids (FA/MnO2 /CDs@AuNPs/CDs) have been synthesized and proven to be excellent photosensitizers for photodynamic therapy applications. Abstract : Carbon-based dot-capped gold nanoparticles (AuNPs/CDs) were synthesized and found to exhibit high singlet oxygen ( 1 O2 ) generation capability owing to the synergistic effect of the strong localized surface plasmon resonance (LSPR) absorption of AuNPs and high 1 O2 yield of CDs. The obtained AuNPs/CDs were further hybridized with folic acid (FA)-modified and CD-capped manganese dioxide nanosheets (FA/MnO2 /CDs). The hybridization-induced aggregation produced a new and strong LSPR absorption peak of AuNPs at around 680 nm. Furthermore, MnO2 nanosheets in the obtained FA/MnO2 /CDs-AuNPs/CDs nanohybrids could react with intracellular H2 O2 to release O2, which could relieve the tumor hypoxia microenvironment. The 1 O2 quantum yield of the nanohybrids under 660 nm laser irradiation was about 1.05% in the absence of H2 O2 and increased to 2.60% in the presence of 1 × 10 −5 mol L −1 H2 O2 . In vitro cell viability studies demonstrate that >95% of HeLa cells were killed by treatment with FA/MnO2 /CDs-AuNPs/CDs under irradiation (660 nm, 2.5 W cm −2 ) for 20 min. The as-developed nanohybrids are thus proved to be promising photosensitizers for photodynamic therapy applications.